PUBLIC DEBT AND ECONOMIC GROWTH: AN EMPIRICAL ASSESSMENT - Al-Zeaud, Hussein Ali (European Scientific Journal, ESJ, 2014)
Being economical policymaker, Government of Jordan claims that public debt has been used mainly to finance productive investment which is expected to enhance economic growth. To investigate the effect of public debt on growth using the per capita income approach, the study augments a growth and debt specifications based on conditional convergence by adding several growth variables. This paper examines the impact of public debt on the performance of the Jordanian economy using new econometric techniques that provide appropriate procedures for estimation and inference. Empirical evidence shows that population growth and public debt have played very crucial role towards economic growth in Jordan. It shows that public debt has promoted economic growth, while population growth has hindered it. Thus, if Jordan is hoping to attain sustained economic growth, positive effect of public debt should be maintained while negative effect of population growth should be reduced.